2022
DOI: 10.3389/fcvm.2022.889597
|View full text |Cite
|
Sign up to set email alerts
|

Non-alcoholic Fatty Liver Disease Is Associated With Cardiovascular Outcomes in Subjects With Prediabetes and Diabetes: A Prospective Community-Based Cohort Study

Abstract: BackgroundThere have been no studies of the effect of non-alcoholic fatty liver disease (NAFLD) on cardiovascular events (CVEs) in patients with pre-diabetes (pre-DM), and diabetes mellitus (DM). We performed a community-based cohort study to evaluate the relationship between NAFLD and CVEs in patients with glucose metabolism disorder.MethodsWe enrolled 71,852 participants from the Kailuan study who had not experienced CVEs, after excluding alcohol abuse and other liver diseases. NAFLD was assessed using abdom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 42 publications
(47 reference statements)
0
5
0
Order By: Relevance
“…However our study differs from these recent studies in several important ways. Several studies have examined this association in population in countries other than the United States ( Song et al, 2022a ; Song et al, 2022b ; Kolluru et al, 2022 ; Succurro et al, 2022 ; Xu et al, 2022 ). While informative, the results of these studies cannot be generalized to the United States population, and typically do not allow for examination by race/ethnicity.…”
Section: Discussionmentioning
confidence: 99%
“…However our study differs from these recent studies in several important ways. Several studies have examined this association in population in countries other than the United States ( Song et al, 2022a ; Song et al, 2022b ; Kolluru et al, 2022 ; Succurro et al, 2022 ; Xu et al, 2022 ). While informative, the results of these studies cannot be generalized to the United States population, and typically do not allow for examination by race/ethnicity.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4]6 Growing evidence indicates that patients with NAFLD are at increased risk for the development of hypertension, coronary heart disease, cardiomyopathy, and cardiac arrhythmias, which clinically result in increased cardiovascular morbidity and mortality. [38][39][40][41] While lifestyle modifications remain the cornerstone of the management of NAFLD, 42 there has been a marked absence of effective pharmacological therapies approved for this condition. 43 Therefore, identifying emerging serum markers for NAFLD might help find high-risk individuals and develop auxiliary prevention or treatment strategies.…”
Section: Discussionmentioning
confidence: 99%
“…CVE was defined previously [ 28 ] as a composite of stroke and MI until December 31, 2019 [ 29 ]. The endpoints of this study were the first appearance of CVE, which was identified by medical staff from the provincial vital statistics data, Tangshan medical insurance system, and Kailuan Group Medical Insurance Information System during the semiannual interviews.…”
Section: Methodsmentioning
confidence: 99%
“…The concentrations of the lipid parameters were determined using an automatic biochemistry analyzer (Hitachi 747, Tokyo, Japan) [ 28 ]. White blood cell counts were measured using an XE-1200 automated hematology analyzer (Sysmex, Kobe, Japan).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation